Comparative cytogenetics of two species of Dermanura (Chiroptera, Phyllostomidae) in Midwestern Brazil - de Sousa, Ricardo Firmino; Venere, Paulo Cesar; Faria, Karina de Cassia (Comparative cytogenetics, 2021)
Dermanura Gervais, 1856 is represented by small frugivorous bats of the Stenodermatinae subfamily. The taxonomy of this group presents controversies and has been subject to changes, especially since the morphological characters evaluated have left gaps that are difficult to fill regarding good species characterization. Previous studies performed in Dermanura cinerea Gervais, 1856 found that the karyotype of this species has a diploid number of chromosomes equal to 30 and 56 autosomal arms. The objective of the present study was to describe, for the first time, the karyotypes of the species Dermanura anderseni (Osgood, 1916) and Dermanura gnoma (Handley, 1987) based on classical cytogenetic markers. For both species, the diploid number found was 2n = 30 and NFa = 56. Two pairs of chromosomes showed markings of the nucleolus organizing regions (AgNORs) in the species D. anderseni and only one pair in D. gnoma , differing from what has already been described for D. cinerea . The two species analyzed here also showed differences in the sex chromosome system, with D. gnoma showing a neo-XY type system while in D. anderseni the classic XY sexual system was observed. In both species, visualization of the constitutive heterochromatin occurred in the pericentromeric region of all chromosomes, as well as in the short arms of the subtelocentric chromosomes. The present work represents an important expansion of karyotypic information for the subfamily Stenodermatinae, bringing chromosomal features that are possible to use in the taxonomic implications of the group.